Aluminum alloy core power cable based on synergistic regulation of mgsi and preparation method thereof
Patent Information
- Application Number
- CN202611126282.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-30
AI Technical Summary
[0009]针对以上不足,本发明提供一种基于MgSi协同调控的铝合金芯电力电缆及其制备方法,解决了现有铝合金电缆中导电率与强度相互制约、难以实现综合性能优化匹配的技术问题
1. 本发明通过优化Mg/Si质量比,实现导体成分设计优化,提高导体综合性能。其中,将Si含量控制在0.40%~1.20%、Mg含量控制在0.10%~0.20%,并将Mg/Si质量比控制在0.15~0.50范围内,使Mg与Si能够形成适量且稳定的Mg2Si强化相。当Mg/Si质量比处于上述范围时,可有效避免析出强化不足或粗大析出相形成,在保持较高导电率的同时提高导体抗拉强度,并保持良好的断裂伸长率和加工性能,为导体综合性能提升提供合理的成分基础。
Smart Images

Figure CN123017618A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of power transmission cable technology, and in particular to an aluminum alloy core power cable based on MgSi synergistic regulation and its preparation method. Background Technology
[0002] In recent years, with the rapid development of new energy power generation, electric vehicle charging infrastructure, rail transit, and the construction of new power systems, power cables are developing towards larger capacity, lighter weight, higher reliability, and longer lifespan. 10kV and 35kV, as important voltage levels in distribution networks and regional transmission networks, are widely used in urban power distribution systems, new energy power generation grid connection projects, industrial park power supply, and rail transit power supply networks. As the core carrier of electrical energy transmission, the conductivity, mechanical properties, and processing and installation performance of power cable conductors directly affect transmission efficiency and operational reliability.
[0003] Currently, copper conductors are the primary material used in power cables, with some using aluminum alloy conductors. While copper conductors offer excellent conductivity, they also present challenges such as high cost, large weight, high resource consumption, and difficult installation. In contrast, aluminum alloy conductors offer advantages such as light weight, abundant resources, low cost, and ease of installation, leading to their increasingly widespread use in power transmission and distribution.
[0004] Existing aluminum alloy conductors typically employ Al-Mg-Si heat-treatable aluminum alloys, with strengthening primarily derived from the Mg2Si precipitate formed by Mg and Si. By controlling the quantity, size, and distribution of the Mg2Si precipitate, the conductor's microstructure and mechanical properties can be effectively improved. However, since Mg and Si elements both participate in precipitation strengthening and influence electron migration within the conductor, a certain constraint always exists between conductivity and strength. How to maintain high conductivity while simultaneously improving conductor strength and achieving good elongation at break is a key technical challenge in the research and application of this type of aluminum alloy conductor.
[0005] Currently, existing technologies still have the following shortcomings: (1) When the content and mass ratio of Mg and Si elements are not properly controlled, the Mg2Si precipitate phase is easily coarsened or unevenly distributed, or even forms a coarse second phase structure. This not only weakens the precipitation strengthening effect, but also increases electron scattering, leading to a decrease in the conductivity of the conductor. At the same time, it affects the strength and plasticity of the conductor, making it difficult to achieve a reasonable match between conductivity and mechanical properties.
[0006] (2) Existing conductor preparation processes mostly employ conventional aging and natural cooling processes, which have limited control over the precipitation kinetics and size distribution of Mg2Si precipitates. This makes it difficult to form fine, dispersed and uniformly distributed reinforcing phases, resulting in difficulties in further optimizing the conductivity and mechanical properties of conductors.
[0007] (3) With the development of new energy power transmission, offshore wind power, photovoltaic power generation and flexible power distribution network, power cables are in operation under complex load, alternating temperature and vibration environment for a long time, which puts forward higher requirements for the conductivity, strength, elongation at break and long-term service stability of the conductor. However, the existing aluminum alloy conductors are still difficult to meet the above performance requirements and cannot meet the application needs under complex working conditions.
[0008] Therefore, there is an urgent need to provide an aluminum alloy core power cable that combines high conductivity, high strength, and excellent plasticity to meet the requirements of 10kV and 35kV power cables for comprehensive conductor performance and long-term operational reliability. Summary of the Invention
[0009] To address the above shortcomings, this invention provides an aluminum alloy core power cable based on MgSi synergistic regulation and its preparation method, solving the technical problem of the mutual constraint between conductivity and strength in existing aluminum alloy cables, making it difficult to achieve optimal matching of comprehensive performance. The specific technical solution is as follows: A power cable with an aluminum alloy core based on MgSi synergistic regulation, wherein the cable comprises, from the inside out, a conductor, a semi-conductive inner shielding layer, a cross-linked polyethylene insulation layer, a semi-conductive outer shielding layer, a metal shielding layer, a filling layer, an isolation layer, an armor layer, and an outer sheath layer.
[0010] The conductor is made of aluminum alloy, and its chemical composition by mass percentage includes: Si: 0.40% to 1.20%; Mg: 0.10% to 0.20%; Fe: ≤0.08%; Cu: 0.01% to 0.05%; the balance being Al and unavoidable impurities; wherein the Mg / Si mass ratio is 0.15 to 0.50.
[0011] Preferably, the chemical composition of the conductor, by mass percentage, includes: Si: 1.00%; Mg: 0.20%; Fe: 0.05%; Cu: 0.025%; with the balance being Al and unavoidable impurities.
[0012] Of the unavoidable impurities, the Mn content is ≤0.03%, the content of other single impurities (including Ti, Cr, Ni, Pb, Sn, etc.) is ≤0.03%, and the total impurity content is ≤0.15%. By controlling the content of impurity elements, inclusions and segregation defects can be reduced, the uniformity of the structure can be improved, and the long-term operational stability of the conductor can be enhanced.
[0013] This invention limits the Mg / Si mass ratio to ensure the formation of an appropriate amount of Mg2Si strengthening phase. When the Mg / Si ratio is too low, insufficient Mg weakens the strengthening effect of Mg2Si precipitation, resulting in limited improvement in conductor strength. Conversely, when the Mg / Si ratio is too high, excess Mg dissolves in the aluminum matrix, increasing electron scattering and leading to uneven precipitate distribution, thus affecting the conductor's conductivity. Therefore, by rationally controlling the Mg / Si ratio, a stable compositional basis can be provided for subsequent precipitate regulation.
[0014] Cable structure adaptation: The cable structure parameters are designed differently to meet the usage requirements of different voltage levels, 10kV and 35kV. (1) Semiconducting inner shielding layer and semiconducting outer shielding layer The semiconductive inner shielding layer has a resistivity of ≤800Ω·m, and the semiconductive outer shielding layer has a resistivity of ≤400Ω·m; these are used to uniformly distribute the electric field between the conductor and the insulating layer, as well as between the insulating layer and the metal shielding layer, thereby reducing local electric field distortion and suppressing partial discharge.
[0015] Specifically, the thickness of both the semi-conductive inner and outer shielding layers of the 10kV cable is 0.7–1.0 mm; the thickness of both the semi-conductive inner and outer shielding layers of the 35kV cable is 0.8–1.1 mm. By optimizing the shielding layer thickness, the electric field homogenization requirements under different voltage levels can be met, thereby improving the operational reliability of the insulation system.
[0016] (2) Cross-linked polyethylene insulation layer The insulation layer is prepared using ultra-clean cross-linked polyethylene (XLPE) insulation material through a three-layer co-extrusion process.
[0017] Specifically, the insulation layer thickness of 10kV cables is 4.2–5.0 mm; the insulation layer thickness of 35kV cables is 10.0–11.0 mm. This structure not only meets the requirements for long-term power frequency withstand voltage and impulse withstand voltage, but also helps to reduce cable outer diameter and material consumption, thus improving product economy.
[0018] (3) Metal shielding layer The metal shielding layer adopts a copper strip shielding structure or a copper wire shielding structure.
[0019] The thickness of the copper strip is 0.10–0.20 mm. For cable specifications with a cross-section of 50–185 mm², a soft copper strip overlapping wrapping structure is preferred; for large cross-section cable specifications of 240–630 mm², a loosely wound copper wire is preferred, and the surface can be tightly bound with copper wire or copper strip wrapped in the opposite direction to improve short-circuit current carrying capacity, thermal stability and electromagnetic shielding performance.
[0020] (4) Armor layer The armor layer adopts a double-layer steel strip wrapping armor structure.
[0021] The steel strip thickness is 0.50–0.80 mm; the metal strip armor should be spirally wrapped in two layers, and the wrapping should be smooth and round, with the middle part of the outer metal strip above the gap of the inner metal strip. The gap ratio of each metal strip layer should not exceed 50%. The armor layer can effectively improve the cable's resistance to pressure, impact, and mechanical damage, meeting the long-term operation requirements of direct burial, trench laying, and complex environments.
[0022] (5) Sheath layer The sheath layer is made of polyvinyl chloride (PVC), polyethylene (PE), or halogen-free low-smoke flame-retardant sheath material.
[0023] Among them: PVC sheath has excellent mechanical and processing properties; PE sheath has excellent weather resistance and resistance to environmental stress cracking; halogen-free low-smoke flame-retardant sheath has good flame-retardant and environmental performance.
[0024] Select appropriate sheath materials according to different laying environments and safety level requirements to meet the application needs of cables in urban power distribution networks, new energy power plants, rail transit and industrial power supply systems.
[0025] The present invention also provides a method for manufacturing the power cable, comprising the following steps: Step S1: Raw material preparation and smelting / refining According to the chemical composition ratio of the conductor, the raw materials are batched and cleaned. Industrial pure aluminum, Al-20Si master alloy, Al-10Mg master alloy, Al-10Fe master alloy and Al-50Cu master alloy are added to the melting furnace for melting. The melting temperature is controlled at 740-770℃. After melting, online rotary blowing is used for refining and degassing. The refining gas is nitrogen or argon. The refining time is 10-18 minutes. After standing for 5-12 minutes, the slag is removed to obtain clean aluminum alloy melt.
[0026] Step S2: Continuous casting and rolling into rods The refined aluminum alloy melt is transported to a continuous casting and rolling mill for continuous casting and rolling, with the casting and rolling temperature controlled at 680-720℃; aluminum alloy casting rods with a diameter of 9.5-15mm are obtained.
[0027] Step S3: Homogenization The aluminum alloy casting rod was placed in a homogenization furnace for heat treatment at a homogenization temperature of 500–540℃ for 3–8 hours, and then air-cooled to room temperature to eliminate component segregation and promote microstructure homogenization.
[0028] Step S4: Cold deformation processing The homogenized aluminum alloy rod is processed using a multi-pass cold rolling and cold drawing process, with the total deformation controlled at 85% to 95%; the cold drawing speed is controlled at 6 to 10 m / min, and finally aluminum alloy monofilaments of the design specifications are obtained, with the monofilament diameter tolerance controlled at ±0.01 mm.
[0029] Step S5: Online Continuous Time-Based Processing The cold-drawn aluminum alloy monofilament is continuously aging in an online aging furnace. The aging temperature is controlled at 180-260℃ and the holding time is 30-180min to promote the formation of uniformly distributed Mg2Si precipitation nuclei of Mg and Si elements.
[0030] Step S6: Gradient cooling treatment After online aging, the conductor undergoes gradient cooling through a primary cooling zone, a secondary cooling zone, and a natural cooling zone. The primary cooling rate is 3–8 °C / min, the secondary cooling rate is 1–5 °C / min, and the third stage involves natural cooling to room temperature to control the size and distribution of the Mg2Si precipitate phase, thereby improving the conductor's conductivity and elongation.
[0031] Step S7: Conductor stranding and compression Multiple aluminum alloy monofilaments are formed into an aluminum alloy core wire using a compaction stranding process. The stranding pitch is 12 to 15 times the core wire diameter, and the compaction coefficient is not less than 0.90. The conductor cross-section of the 10kV cable is 70 to 500 mm², and the conductor cross-section of the 35kV cable is 70 to 630 mm².
[0032] Step S8: Co-extrusion of the insulation layer and inner and outer shielding layers The treated aluminum alloy core wire is simultaneously extruded with a three-layer co-extrusion process, consisting of a semi-conductive inner shielding layer, a cross-linked polyethylene insulation layer, and a semi-conductive outer shielding layer.
[0033] Specifically: for 10kV cables, the thickness of the semi-conductive inner shield and the semi-conductive outer shield is 0.7–1.0 mm, and the thickness of the insulation layer is 4.2–5.0 mm; for 35kV cables, the thickness of the semi-conductive inner shield and the semi-conductive outer shield is 0.8–1.1 mm, and the thickness of the insulation layer is 10.0–11.0 mm; the extrusion temperature is controlled at 120–150℃.
[0034] Step S9: Copper tape shielding wrapping After extrusion, continuous cross-linking treatment is carried out, with the cross-linking temperature controlled at 190-320℃ and held for 20-40 minutes. After cross-linking, the material is cooled and shaped, and a metal shielding layer is set outside the semi-conductive outer shielding layer.
[0035] The metal shielding layer adopts a soft copper strip shielding structure or a copper wire shielding structure, and the copper strip thickness is 0.10 to 0.20 mm.
[0036] Step S10: Cable Formation Three metal-shielded wire cores are twisted into a cable with a cable pitch ratio of no more than 18. At the same time, polypropylene filler rope is filled between the three cores and wrapped with non-woven fabric for fixation to improve the stability of the cable core structure.
[0037] Step S11: Preparation of the isolation layer, armor layer and outer sheath The process involves sequentially extruding the isolation layer, steel strip armor, and outer sheath; the extrusion temperature of the isolation layer is 160–190℃; the thickness of the steel strip is 0.50–0.80 mm; the outer sheath is made of PVC sheath material, PE sheath material, or halogen-free low-smoke flame-retardant sheath material, and the sheath thickness is 2.9–5.1 mm.
[0038] Step S12: Finished Product Inspection The manufactured cable is subjected to tests for conductor DC resistance, conductivity, tensile strength, elongation at break, power frequency withstand voltage, partial discharge, insulation resistance, structural dimensions, and spark. The finished cable is obtained after passing the tests.
[0039] This invention regulates the Mg2Si precipitation process through online continuous aging and gradient cooling. After cold working, the wire enters a continuous aging furnace for online continuous aging treatment, which causes Mg and Si atoms to diffuse and form uniformly distributed Mg2Si precipitation nuclei, increasing the number of precipitated phase nuclei and reducing the solid solution residue of Mg and Si elements.
[0040] After online continuous aging is completed, the conductor undergoes gradient cooling treatment in three stages: primary cooling, secondary cooling and natural cooling. By controlling the cooling rate at different stages, the growth process of Mg2Si precipitates is regulated, the formation of coarse precipitates is suppressed, the precipitates are kept in a fine and dispersed state, and the uniformity of the structure is improved.
[0041] Through the above-mentioned component design and process control, the present invention forms the following synergistic mechanism: Mg and Si form fine and dispersed Mg2Si precipitates, online continuous aging promotes uniform nucleation of the precipitates, gradient cooling further controls the size and distribution of the precipitates, reduces the solid solution residue of Mg and Si elements, reduces electron scattering, and enables the conductor to obtain high tensile strength while maintaining high conductivity and good elongation at break, thus achieving coordinated optimization of conductivity and mechanical properties.
[0042] The cable conductor obtained by this invention has a conductivity ≥62.0% IACS, a tensile strength ≥118MPa, and an elongation at break ≥15%. It also has excellent flexibility, processing performance, and long-term operational stability, and can meet the long-term safe operation requirements of 10kV and 35kV power systems.
[0043] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention optimizes the conductor composition design and improves the overall performance of the conductor by optimizing the Mg / Si mass ratio. Specifically, the Si content is controlled within 0.40%–1.20%, the Mg content within 0.10%–0.20%, and the Mg / Si mass ratio within the range of 0.15–0.50, allowing Mg and Si to form a suitable and stable Mg2Si strengthening phase. When the Mg / Si mass ratio is within the above range, insufficient precipitation strengthening or the formation of coarse precipitates can be effectively avoided. This maintains high conductivity while improving the tensile strength of the conductor, and also maintains good elongation at break and processing performance, providing a reasonable compositional basis for improving the overall performance of the conductor.
[0044] 2. This invention employs a combination of online continuous aging and gradient cooling processes to achieve precise control of Mg2Si precipitates. Specifically, the online continuous aging treatment after cold working of the conductor promotes uniform nucleation of the Mg2Si precipitates. Subsequently, a gradient cooling process is used to regulate the growth of the Mg2Si precipitates, suppressing the formation of coarse precipitates and ensuring that the precipitates remain fine, dispersed, and uniformly distributed. This process helps reduce the residual solid solution of Mg and Si elements and electron scattering, improves the uniformity of the microstructure, achieves coordinated optimization of the conductor's conductivity and mechanical properties, and enhances the long-term service stability of the conductor.
[0045] 3. This invention employs a power cable structure design suitable for 10kV and 35kV voltage levels, achieving a good match between conductor performance and cable structure. The cable utilizes a multi-layered composite structure consisting of a semi-conductive inner shielding layer, a cross-linked polyethylene insulation layer, a semi-conductive outer shielding layer, a metallic shielding layer, an armor layer, and an outer sheath layer. The insulation thickness and shielding structure design are optimized for different voltage levels, effectively meeting the requirements for power frequency withstand voltage, electric field homogenization, and mechanical protection, thus improving the safety and reliability of the cable in complex operating environments. Furthermore, the process of this invention is mature and stable, suitable for large-scale industrial production. Attached Figure Description
[0046] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0047] Figure 1 This is a process flow diagram for manufacturing the aluminum alloy core power cable of the present invention; Figure 2The figures show the tensile strength and elongation of the aluminum alloy cable materials prepared in Examples 1-4 and Comparative Examples 1-4. In all examples, the soft tensile strength of the aluminum alloy cable materials is above 118 MPa, and the elongation is ≥15%. Both the tensile strength and elongation are within the range specified by national standards. Figure 3 The stress-elongation diagram is shown for the tensile test of the aluminum alloy core power cable in Example 3. Detailed Implementation
[0048] The specific embodiments of the present invention are described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. Unless otherwise defined, all technical terms used below have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing specific embodiments only and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, all raw materials, reagents, instruments, and equipment used in the present invention are commercially available or can be prepared by existing methods.
[0049] The raw materials used in the following examples are: industrial pure aluminum (Al≥99.70%), Al-10Fe master alloy (Fe content 9.5~10.5%), Al-20Si master alloy (Si content 19.0~21.0%), Al-10Mg master alloy (Mg content 9.5~10.5%), and Al-50Cu master alloy (Cu content 48.0~51.0%), all of which are commercially available industrial-grade products.
[0050] Example 1 This embodiment discloses a high-conductivity, high-elongation aluminum alloy core power cable. The chemical composition (mass percentage) of its conductor is: Al-0.40Si-0.20Mg-0.05Fe-0.025Cu, with the balance being Al and unavoidable impurities. The Mg / Si mass ratio is 0.50. The cable is prepared by: Step S1: Raw material preparation and smelting / refining Based on a total batch size of 480 kg, weigh the following according to the target composition ratio: 458.16 kg of industrial pure aluminum; 9.60 kg of Al-20Si master alloy; 9.60 kg of Al-10Mg master alloy; 0.24 kg of Al-50Cu master alloy; and 2.40 kg of Al-10Fe master alloy. Clean the surfaces of each raw material to remove oxide scale, oil, and impurities before use.
[0051] Industrial pure aluminum was then added to a melting furnace, heated to 740℃ to melt, and held at that temperature for 25 minutes. Al-20Si, Al-10Mg, Al-50Cu, and Al-10Fe master alloys were added sequentially, with stirring for 3 minutes after each addition. After melting, the mixture was refined using argon rotary jet for 18 minutes, allowed to stand for 10 minutes, and then the slag was removed to obtain a pure aluminum alloy melt.
[0052] Step S2: Continuous casting and rolling into rods The refined aluminum alloy melt is transported to the continuous casting and rolling mill for continuous casting and rolling. The casting and rolling temperature is controlled at 680-720℃ to obtain aluminum alloy cast rods. Step S3: Homogenization The aluminum alloy rod was placed in a homogenization furnace for heat treatment. The homogenization temperature was controlled at 520℃; the holding time was 5 hours; and then it was air-cooled to room temperature. The homogenization treatment eliminated casting segregation and promoted the uniform distribution of Mg and Si elements.
[0053] Step S4: Cold deformation processing Aluminum alloy monofilaments were prepared using a multi-pass continuous drawing process. The drawing speed was controlled at 10 m / min; the total deformation was not less than 90%; and the final aluminum alloy monofilaments were obtained with dimensional tolerances controlled within ±0.01 mm.
[0054] Step S5: Online Continuous Time-Based Processing The drawn aluminum alloy monofilaments are directly fed into an online continuous aging apparatus. The aging temperature is controlled at 260℃, and the holding time is 90 minutes. Online continuous aging promotes the formation of fine and dispersed Mg2Si precipitates and controls their size distribution, thereby improving the conductor's conductivity and elongation at break.
[0055] Step S6: Gradient cooling treatment After online aging, the conductor undergoes gradient cooling through a primary cooling zone, a secondary cooling zone, and a natural cooling zone. The primary cooling rate is 5℃ / min, the secondary cooling rate is 3℃ / min, and the third stage involves natural cooling to room temperature to control the size and distribution of the Mg2Si precipitate phase, thereby improving the conductor's conductivity and elongation.
[0056] Step S7: Conductor stranding and compression Multiple aluminum alloy monofilaments are twisted together using a compaction stranding process to form an aluminum alloy conductor. The stranding pitch is 14 times the conductor diameter; the compaction factor is 0.90. After stranding, the conductor is cleaned and dried.
[0057] Step S8: Co-extrusion of the insulation layer and inner and outer shielding layers A three-layer co-extrusion process is used to simultaneously extrude a semi-conductive inner shielding layer, a cross-linked polyethylene insulation layer, and a semi-conductive outer shielding layer onto the treated aluminum alloy conductor.
[0058] For 10kV cables: the thickness of the semi-conductive inner shielding layer is 0.8mm; the thickness of the semi-conductive outer shielding layer is 0.8mm; and the thickness of the cross-linked polyethylene insulation layer is 4.5mm.
[0059] For 35kV cables: the thickness of the semi-conductive inner shield is 1.0mm; the thickness of the semi-conductive outer shield is 1.0mm; and the thickness of the cross-linked polyethylene insulation layer is 10.5mm. The extrusion temperature is controlled between 135 and 145℃.
[0060] Step S9: Copper tape shielding wrapping After the three-layer co-extrusion is completed, the wire core undergoes continuous cross-linking treatment. The cross-linking temperature is controlled at 190-200℃; and the temperature is maintained for 35 minutes.
[0061] Subsequently, a metal shielding layer is set outside the semiconductive outer shielding layer. The metal shielding layer adopts a soft copper strip shielding structure or a copper wire shielding structure, and the copper strip thickness is not less than 0.10mm.
[0062] Step S10: Cable Formation The three-core insulated wires with metal shielding are twisted into a cable using a cabling machine with a cable pitch ratio of 18. At the same time, polypropylene filler rope is filled into the gaps between the three cores to form a filler layer, and non-woven fabric tape is used for fixation.
[0063] Step S11: Preparation of the isolation layer, armor layer and outer sheath The process involves sequentially extruding the isolation layer, steel strip armor, and outer sheath; the extrusion temperature of the isolation layer is 160–190℃; the thickness of the steel strip is 0.50–0.80 mm; the outer sheath is made of PVC sheath material, PE sheath material, or halogen-free low-smoke flame-retardant sheath material, and the sheath thickness is 2.9–5.1 mm.
[0064] Step S12: Finished Product Inspection The manufactured cable is subjected to tests for conductor DC resistance, conductivity, tensile strength, elongation at break, power frequency withstand voltage, partial discharge, insulation resistance, structural dimensions, and spark.
[0065] Example 2 This embodiment discloses a high-conductivity, high-elongation aluminum alloy core power cable. The chemical composition (mass percentage) of its conductor is: Al-0.60Si-0.20Mg-0.05Fe-0.025Cu, with the balance being Al and unavoidable impurities. The Mg / Si mass ratio is 0.33. Compared to the composition of Example 1, the Si content is increased. The cable is prepared by: Step S1: Raw material pretreatment Based on a total batch size of 480 kg, weigh the following according to the target composition ratio: 453.36 kg of industrial pure aluminum; 14.40 kg of Al-20Si master alloy; 9.60 kg of Al-10Mg master alloy; 0.24 kg of Al-50Cu master alloy; and 2.40 kg of Al-10Fe master alloy. Clean the surfaces of each raw material to remove oxide scale, oil, and impurities before use.
[0066] The remaining steps are the same as in Example 1.
[0067] Example 3 This embodiment discloses a high-conductivity, high-elongation aluminum alloy core power cable. The chemical composition (mass percentage) of its conductor is: Al-1Si-0.20Mg-0.05Fe-0.025Cu, with the balance being Al and unavoidable impurities. The Mg / Si mass ratio is 0.2. Compared to the composition of Example 1, the Si content is increased. The cable is prepared by: Step S1: Raw material pretreatment Based on a total batch size of 480 kg, weigh the following according to the target composition ratio: 443.76 kg of industrial pure aluminum; 24.0 kg of Al-20Si master alloy; 9.60 kg of Al-10Mg master alloy; 0.24 kg of Al-50Cu master alloy; and 2.40 kg of Al-10Fe master alloy. Clean the surfaces of each raw material to remove oxide scale, oil, and impurities before use.
[0068] The remaining steps are the same as in Example 1.
[0069] Example 4 This embodiment discloses a high-conductivity, high-elongation aluminum alloy core power cable. The chemical composition (mass percentage) of its conductor is: Al-1.2Si-0.20Mg-0.05Fe-0.025Cu, with the balance being Al and unavoidable impurities. The Mg / Si mass ratio is 0.17. Compared to the composition of Example 1, the Si content is increased. The cable is prepared by: Step S1: Raw material pretreatment Based on a total batch size of 480 kg, weigh the following components according to the target composition ratio: 438.96 kg of industrial pure aluminum; 28.8 kg of Al-20Si master alloy; 9.60 kg of Al-10Mg master alloy; 0.24 kg of Al-50Cu master alloy; and 2.40 kg of Al-10Fe master alloy. Clean the surfaces of each raw material to remove oxide scale, oil, and impurities before use.
[0070] The remaining steps are the same as in Example 1.
[0071] Comparative Example 1 This comparative example discloses an aluminum alloy core power cable. The chemical composition (mass percentage) of its conductor is: Al-1Si-0.10Mg-0.05Fe-0.025Cu, with the balance being Al and unavoidable impurities. The Mg / Si mass ratio is 0.1, which is lower than the set range (0.15-0.50) compared to the example. The rest is the same as in Example 1. The cable is prepared by: Step S1: Raw material pretreatment Based on a total batch size of 480 kg, weigh the following components according to the target composition ratio: 448.56 kg of industrial pure aluminum; 24.0 kg of Al-20Si master alloy; 4.80 kg of Al-10Mg master alloy; 0.24 kg of Al-50Cu master alloy; and 2.40 kg of Al-10Fe master alloy. Clean the surfaces of each raw material to remove oxide scale, oil, and impurities before use.
[0072] The remaining steps are the same as in Example 1.
[0073] Comparative Example 2 This comparative example describes an aluminum alloy core power cable. The chemical composition (mass percentage) of its conductor is: Al-1Si-0.30Mg-0.05Fe-0.025Cu, with the balance being Al and unavoidable impurities. The Mg / Si mass ratio is 0.3. Compared to the example, although the Mg / Si mass ratio is within the set range (Mg / Si mass ratio 0.15~0.50), the Mg content exceeds the set value (Mg 0.10%~0.20%). The rest is the same as in Example 1. The cable is prepared by:
[0074] Step S1: Raw material pretreatment Based on a total batch size of 480 kg, weigh the following according to the target composition ratio: 438.96 kg of industrial pure aluminum; 24.0 kg of Al-20Si master alloy; 14.4 kg of Al-10Mg master alloy; 0.24 kg of Al-50Cu master alloy; and 2.40 kg of Al-10Fe master alloy. Clean the surfaces of each raw material to remove oxide scale, oil, and impurities before use.
[0075] The remaining steps are the same as in Example 1.
[0076] Comparative Example 3 The aluminum alloy core wire composition of this comparative example of an aluminum alloy core power cable is Al-1Si-0.2Mg-0.05Fe-0.025Cu (same as Example 3). Compared with Example 3, the online continuous aging and gradient cooling are eliminated during preparation, and ordinary annealing is used instead, as detailed below: Step S1: Raw material preparation and smelting / refining Based on a total batch size of 480 kg, weigh the following according to the target composition ratio: 443.76 kg of industrial pure aluminum; 24.0 kg of Al-20Si master alloy; 9.60 kg of Al-10Mg master alloy; 0.24 kg of Al-50Cu master alloy; and 2.40 kg of Al-10Fe master alloy. Clean the surfaces of each raw material to remove oxide scale, oil, and impurities before use.
[0077] Industrial pure aluminum was then added to a melting furnace, heated to 740℃ to melt, and held at that temperature for 25 minutes. Al-20Si, Al-10Mg, Al-50Cu, and Al-10Fe master alloys were added sequentially, with stirring for 3 minutes after each addition. After melting, the mixture was refined using argon rotary jet for 18 minutes, allowed to stand for 10 minutes, and then the slag was removed to obtain a pure aluminum alloy melt.
[0078] Step S2: Continuous casting and rolling into rods The refined aluminum alloy melt is transported to the continuous casting and rolling mill for continuous casting and rolling. The casting and rolling temperature is controlled at 680-720℃ to obtain aluminum alloy cast rods. Step S3: Homogenization The aluminum alloy rod was placed in a homogenization furnace for heat treatment. The homogenization temperature was controlled at 520℃; the holding time was 5 hours; and then it was air-cooled to room temperature. The homogenization treatment eliminated casting segregation and promoted the uniform distribution of Mg and Si elements.
[0079] Step S4: Cold deformation processing Aluminum alloy monofilaments were prepared using a multi-pass continuous drawing process. The drawing speed was controlled at 10 m / min; the total deformation was not less than 90%; and the final aluminum alloy monofilaments were obtained with dimensional tolerances controlled within ±0.01 mm.
[0080] Step S5: Normal annealing After drawing, the aluminum alloy monofilaments are annealed in an annealing furnace at a temperature of 260℃ for 90 minutes. No online continuous aging process is used during annealing; only conventional constant-temperature holding is employed to eliminate some of the work hardening and residual stress generated during drawing, thereby improving the conductor's plasticity.
[0081] After annealing, the aluminum alloy monofilament is cooled to room temperature in the furnace without gradient cooling.
[0082] Step S6: Conductor stranding and compression Multiple aluminum alloy monofilaments are stranded together using a compaction stranding process to form a 6-series aluminum alloy conductor. The stranding pitch is 14 times the conductor diameter; the compaction factor is 0.90. After stranding, the conductor is cleaned and dried.
[0083] Step S7: Co-extrusion of the insulation layer and inner and outer shielding layers A three-layer co-extrusion process is used to simultaneously extrude a semi-conductive inner shielding layer, a cross-linked polyethylene insulation layer, and a semi-conductive outer shielding layer onto the treated aluminum alloy conductor.
[0084] For 10kV cables: the thickness of the semi-conductive inner shielding layer is 0.8mm; the thickness of the semi-conductive outer shielding layer is 0.8mm; and the thickness of the cross-linked polyethylene insulation layer is 4.5mm.
[0085] For 35kV cables: the thickness of the semi-conductive inner shield is 1.0mm; the thickness of the semi-conductive outer shield is 1.0mm; and the thickness of the cross-linked polyethylene insulation layer is 10.5mm. The extrusion temperature is controlled between 135 and 145℃.
[0086] Step S8: Copper tape shielding wrapping After the three-layer co-extrusion is completed, the wire core undergoes continuous cross-linking treatment. The cross-linking temperature is controlled at 190-200℃; and the temperature is maintained for 35 minutes.
[0087] Subsequently, a metal shielding layer is set outside the semiconductive outer shielding layer. The metal shielding layer adopts a soft copper strip shielding structure or a copper wire shielding structure, and the copper strip thickness is not less than 0.10mm.
[0088] Step S9: Cable Formation The three-core insulated wires with metal shielding are twisted into a cable using a cabling machine with a cable pitch ratio of 18. At the same time, polypropylene filler rope is filled into the gaps between the three cores to form a filler layer, and non-woven fabric tape is used for fixation.
[0089] Step S10: Preparation of the isolation layer, armor layer and outer sheath The process involves sequentially extruding the isolation layer, steel strip armor, and outer sheath; the extrusion temperature of the isolation layer is 160–190℃; the thickness of the steel strip is 0.50–0.80 mm; the outer sheath is made of PVC sheath material, PE sheath material, or halogen-free low-smoke flame-retardant sheath material, and the sheath thickness is 2.9–5.1 mm.
[0090] Step S11: Finished Product Inspection The manufactured cable is subjected to tests for conductor DC resistance, conductivity, tensile strength, elongation at break, power frequency withstand voltage, partial discharge, insulation resistance, structural dimensions, and spark.
[0091] Comparative Example 4 The aluminum alloy core wire composition of this comparative example of an aluminum alloy core power cable is Al-1Si-0.2Mg-0.05Fe-0.025Cu (same as Example 3). Compared with Example 3, the online continuous aging and gradient cooling are eliminated during preparation, and no annealing treatment is performed. The details are as follows: Step S1: Raw material preparation and smelting / refining Based on a total batch size of 480 kg, weigh the following according to the target composition ratio: 443.76 kg of industrial pure aluminum; 24.0 kg of Al-20Si master alloy; 9.60 kg of Al-10Mg master alloy; 0.24 kg of Al-50Cu master alloy; and 2.40 kg of Al-10Fe master alloy. Clean the surfaces of each raw material to remove oxide scale, oil, and impurities before use.
[0092] Industrial pure aluminum was then added to a melting furnace, heated to 740℃ to melt, and held at that temperature for 25 minutes. Al-20Si, Al-10Mg, Al-50Cu, and Al-10Fe master alloys were added sequentially, with stirring for 3 minutes after each addition. After melting, the mixture was refined using argon rotary jet for 18 minutes, allowed to stand for 10 minutes, and then the slag was removed to obtain a pure aluminum alloy melt.
[0093] Step S2: Continuous casting and rolling into rods The refined aluminum alloy melt is transported to the continuous casting and rolling mill for continuous casting and rolling. The casting and rolling temperature is controlled at 680-720℃ to obtain aluminum alloy cast rods. Step S3: Homogenization The aluminum alloy rod was placed in a homogenization furnace for heat treatment. The homogenization temperature was controlled at 520℃; the holding time was 5 hours; and then it was air-cooled to room temperature. The homogenization treatment eliminated casting segregation and promoted the uniform distribution of Mg and Si elements.
[0094] Step S4: Cold deformation processing Aluminum alloy monofilaments were prepared using a multi-pass continuous drawing process. The drawing speed was controlled at 10 m / min; the total deformation was not less than 90%; and the final aluminum alloy monofilaments were obtained with dimensional tolerances controlled within ±0.01 mm.
[0095] Step S5: Conductor stranding and compression Multiple aluminum alloy monofilaments are stranded together using a compaction stranding process to form a 6-series aluminum alloy conductor. The stranding pitch is 14 times the conductor diameter; the compaction factor is 0.90. After stranding, the conductor is cleaned and dried.
[0096] Step S6: Co-extrusion of the insulation layer and inner and outer shielding layers A three-layer co-extrusion process is used to simultaneously extrude a semi-conductive inner shielding layer, a cross-linked polyethylene insulation layer, and a semi-conductive outer shielding layer onto the treated aluminum alloy conductor.
[0097] For 10kV cables: the thickness of the semi-conductive inner shielding layer is 0.8mm; the thickness of the semi-conductive outer shielding layer is 0.8mm; and the thickness of the cross-linked polyethylene insulation layer is 4.5mm.
[0098] For 35kV cables: the thickness of the semi-conductive inner shield is 1.0mm; the thickness of the semi-conductive outer shield is 1.0mm; and the thickness of the cross-linked polyethylene insulation layer is 10.5mm. The extrusion temperature is controlled between 135 and 145℃.
[0099] Step S7: Copper tape shielding wrapping After the three-layer co-extrusion is completed, the wire core undergoes continuous cross-linking treatment. The cross-linking temperature is controlled at 190-200℃; and the temperature is maintained for 35 minutes.
[0100] Subsequently, a metal shielding layer is set outside the semiconductive outer shielding layer. The metal shielding layer adopts a soft copper strip shielding structure or a copper wire shielding structure, and the copper strip thickness is not less than 0.10mm.
[0101] Step S8: Cable Formation The three-core insulated wires with metal shielding are twisted into a cable using a cabling machine with a cable pitch ratio of 18. At the same time, polypropylene filler rope is filled into the gaps between the three cores to form a filler layer, and non-woven fabric tape is used for fixation.
[0102] Step S9: Preparation of the isolation layer, armor layer and outer sheath The process involves sequentially extruding the isolation layer, steel strip armor, and outer sheath; the extrusion temperature of the isolation layer is 160–190℃; the thickness of the steel strip is 0.50–0.80 mm; the outer sheath is made of PVC sheath material, PE sheath material, or halogen-free low-smoke flame-retardant sheath material, and the sheath thickness is 2.9–5.1 mm.
[0103] Step S10: Finished Product Inspection The manufactured cable is subjected to tests for conductor DC resistance, conductivity, tensile strength, elongation at break, power frequency withstand voltage, partial discharge, insulation resistance, structural dimensions, and spark.
[0104] The alloy formulations for each embodiment and comparative example are shown in Table 1: Table 1. Alloy formulations (kg) for the examples and comparative examples The performance of the cables prepared in each embodiment and comparative example was tested, and the results are shown in Table 2: Table 2. Test data of mechanical properties and conductivity of 35kV and 10kV aluminum alloy core power cables at room temperature (20℃). Based on Table 2 Figure 2 and 3 The results show that the aluminum alloy core power cables prepared in Examples 1-4 of the present invention and Comparative Examples 1-4 have certain differences in conductivity, tensile strength and elongation. Different Mg and Si contents and preparation processes have an impact on the overall performance of the conductor.
[0105] In Example 1, the Si content was 0.40%, the Mg content was 0.20%, the conductor conductivity was 62.9% IACS, the tensile strength was 118 MPa, and the elongation was 18.2%. Due to the low Si content, the number of Mg2Si precipitates that can be formed is small, and the precipitation strengthening effect is relatively limited. Therefore, the conductor has high conductivity and good plasticity, but relatively low tensile strength.
[0106] In Example 2, the Si content was increased to 0.60%, the Mg content remained at 0.20%, the conductor conductivity was 62.2% IACS, the tensile strength increased to 128 MPa, and the elongation was 16.0%. With the increase in Si content, more Mg2Si precipitates could be formed, enhancing the precipitation strengthening effect and increasing the conductor's tensile strength. Simultaneously, due to changes in precipitation behavior and the content of solid solution atoms, the conductivity decreased slightly compared to Example 1, but remained above 62% IACS.
[0107] In Example 3, the Si content was increased to 1.00%, the Mg content remained at 0.20%, the conductor conductivity was 62.6% IACS, the tensile strength reached 138 MPa, and the elongation reached 17.3%. At this point, Mg and Si formed a suitable quantity of Mg2Si precipitates with small size and uniform distribution. Combined with online continuous aging and gradient cooling processes, the size and distribution of the precipitates were effectively controlled, reducing the influence of solid-solution Mg and Si atoms and structural defects on electron migration, thus achieving a better match between the conductor conductivity, tensile strength, and elongation.
[0108] In Example 4, the Si content was increased to 1.20%, while the Mg content remained at 0.20%. The conductor conductivity was 62.0% IACS, the tensile strength was 140 MPa, and the elongation was 15.3%. With further increases in Si content, the precipitation strengthening effect continued to enhance, slightly increasing the conductor's tensile strength. However, limited by the Mg content, some Si did not participate in the precipitation of Mg₂Si and formed a certain amount of the second phase, resulting in a decrease in the conductor conductivity and elongation. This indicates that further increases in Si content are beneficial for improving strength, but reduce conductivity and ductility.
[0109] In Comparative Example 1, the Si content was maintained at 1.00%, while the Mg content was reduced to 0.10%. The conductor conductivity was 62.7% IACS, the tensile strength was 112 MPa, and the elongation was 19.1%. Due to the insufficient Mg content, the number of Mg2Si precipitates that could be formed decreased, weakening the precipitation strengthening effect and thus reducing the conductor's tensile strength. Simultaneously, the reduced solid-solution Mg content weakened electron scattering, leading to a slight increase in conductivity and elongation. This demonstrates that while excessively low Mg content is beneficial for improving conductivity and plasticity, it is difficult to achieve high tensile strength.
[0110] In Comparative Example 2, the Si content remained at 1.00%, while the Mg content was increased to 0.30%. The conductor conductivity was 61.5% IACS, the tensile strength was 142 MPa, and the elongation was 8.1%. With the increase of Mg content, the precipitation strengthening effect of Mg2Si was further enhanced, which improved the tensile strength of the conductor. However, the excess Mg increased the number of solid solution atoms and precipitated phases, enhanced electron scattering, and significantly reduced plasticity. Therefore, both the conductivity and elongation decreased.
[0111] Comparative Example 3 has the same chemical composition as Example 3, but instead of online continuous aging and gradient cooling after drawing, it underwent ordinary annealing at 260 °C followed by furnace cooling. Test results showed that its conductivity was 61.9% IACS, tensile strength was 145 MPa, and elongation was 10.2%. While ordinary annealing can eliminate residual stress from cold working to some extent, the lack of synergistic control of the precipitation process by online continuous aging and gradient cooling makes the Mg2Si precipitates prone to coarsening and local aggregation during heat preservation and furnace cooling, resulting in uneven precipitate size distribution. Simultaneously, the precipitation kinetics during furnace cooling are difficult to control precisely, causing some Mg and Si elements to remain in a solid solution state, accompanied by high microstructure inhomogeneity, leading to increased electron scattering and decreased conductivity. Furthermore, the coarse precipitates easily become obstacles to dislocation movement and stress concentration sources, weakening the material's plasticity and significantly reducing the elongation at break. In contrast, Example 3 employs an online continuous aging process combined with gradient cooling, which promotes the fine, dispersed, and uniform distribution of Mg2Si precipitates. This reduces the influence of solid solution atoms on electron migration and avoids coarsening of the precipitates, thus improving the uniformity of the microstructure. Therefore, while maintaining a high tensile strength (138 MPa), the conductivity is increased to 62.6% IACS and the elongation is increased to 17.3%, achieving a good balance between conductivity, mechanical properties, and plasticity.
[0112] Comparative Example 4 has the same chemical composition as Example 3, but no heat treatment was performed after drawing, and the conductor remained in a cold-worked state. Test results showed a conductivity of 52.8% IACS, a tensile strength of 290 MPa, and an elongation of only 2.0%. Due to the extremely high density of dislocations, lattice distortion, and residual stress introduced by extensive cold working deformation, a significant work hardening effect was formed, greatly increasing the tensile strength of the conductor. However, the high density of dislocations and lattice defects significantly enhanced electron scattering, while Mg and Si elements remained mainly in a solid solution state, failing to form stable, fine Mg2Si precipitates, further reducing electron migration ability and leading to a significant decrease in conductivity. Furthermore, the large accumulation of defects in the cold-worked microstructure severely deteriorated the material's plasticity, making it prone to crack initiation and rapid propagation along high-stress regions. Therefore, the elongation at break was only 2.0%, which is insufficient to meet the requirements for subsequent stranding and long-term service of the cable conductor. In contrast, Example 3, through online continuous aging and gradient cooling processes, effectively eliminated some work hardening and residual stress while retaining appropriate strengthening effects. It also achieved a refined and uniformly dispersed distribution of the Mg2Si precipitates, resulting in a conductor with a conductivity of 62.6% IACS, a tensile strength of 138 MPa, and an elongation at break of 17.3%. This demonstrates an optimal balance between conductivity, mechanical properties, and processing performance, highlighting the significant advantages of the process described in this invention. A comprehensive comparison reveals that the Mg / Si element ratio and heat treatment process jointly determine the overall performance of aluminum alloy conductors. With increasing Si content, the strengthening effect of Mg2Si precipitation gradually increases, leading to a continuous improvement in conductor strength. When the Mg / Si ratio is appropriate, a moderate number of small and uniformly distributed Mg2Si precipitates can be formed, achieving a good balance between conductivity, tensile strength, and elongation at break. When the Mg / Si ratio deviates from the appropriate range, the precipitation behavior changes, the microstructure uniformity decreases, and both conductivity and plasticity are adversely affected. On the other hand, compared to ordinary annealing, online continuous aging combined with gradient cooling can more effectively control the Mg2Si precipitation process, optimize the size and distribution of precipitates, and improve microstructure uniformity. Compared to the cold-worked state without heat treatment, it can effectively reduce the adverse effects of work hardening and microstructural defects, significantly improving conductivity and elongation at break while maintaining high strength.
[0113] Therefore, the aluminum alloy conductor prepared in Example 3 has a conductivity of 62.6% IACS, a tensile strength of 138 MPa, and an elongation of 17.3%. The conductivity, tensile strength, and elongation have a good matching relationship, which can meet the application requirements of 10-35 kV power cable conductors for conductivity, mechanical properties, and processing performance.
[0114] The foregoing description of specific exemplary embodiments of the invention is for illustrative and explanatory purposes. These descriptions are not intended to limit the invention to the precise forms disclosed, and it will be apparent that many changes and variations can be made in accordance with the foregoing teachings. The exemplary embodiments were chosen and described in order to explain the specific principles of the invention and its practical application, thereby enabling those skilled in the art to implement and utilize various different exemplary embodiments of the invention, as well as various different choices and variations. The scope of the invention is intended to be defined by the claims and their equivalents.
Claims
1. A power cable with an aluminum alloy core based on MgSi synergistic regulation, wherein the cable comprises, from the inside out, a conductor, a semi-conductive inner shielding layer, a cross-linked polyethylene insulation layer, a semi-conductive outer shielding layer, a metallic shielding layer, a filling layer, an isolation layer, an armor layer, and an outer sheath layer, characterized in that, The chemical composition of the conductor, by mass percentage, includes: Si 0.40%–1.20%, Mg 0.10%–0.20%, Fe ≤0.08%, Cu 0.01%–0.05%, with the balance being Al and unavoidable impurities, the total mass fraction of impurities not exceeding 0.15%, and the Mg / Si mass ratio being 0.15–0.
50.
2. A method for preparing an aluminum alloy core power cable as described in claim 1, characterized in that, Includes the following steps: Step S1, Raw material preparation and smelting and refining: After the conductor is prepared according to the chemical composition ratio, it is smelted, refined and degassed to obtain aluminum alloy melt; Step S2, continuous casting and rolling into rods: The aluminum alloy melt is continuously cast and rolled to obtain an aluminum alloy cast rod; Step S3, Homogenization treatment: The aluminum alloy casting rod is heat-treated and then cooled to room temperature; Step S4, cold deformation processing: The homogenized aluminum alloy casting rod is cold rolled and cold drawn to obtain hard aluminum alloy wire; Step S5: Online continuous aging treatment: The hard aluminum alloy wire is subjected to online continuous aging treatment at an aging temperature of 180-260℃ and a holding time of 30-180min. Step S6, Gradient Cooling Treatment: After aging, the conductor is sequentially passed through multiple cooling zones for gradient cooling. The first stage cooling rate is 3-8℃ / min, the second stage cooling rate is 1-5℃ / min, and the third stage is natural cooling to room temperature, thus obtaining the conductor. Step S7: Preparation of finished cable: The conductor is stranded and compressed, the insulation layer and the inner and outer shielding layers are co-extruded, copper tape shielding is wrapped, stranded into a cable, and after extruding the isolation layer, steel tape armor layer and outer sheath layer, the performance is tested to obtain the finished cable.
3. The method for preparing an aluminum alloy core power cable according to claim 2, characterized in that, In step S1, the raw material preparation and smelting refining are as follows: After the raw materials are prepared according to the proportion of conductor chemical composition, industrial pure aluminum, Al-Si master alloy, Al-Mg master alloy, Al-Fe master alloy and Al-Cu master alloy are added to the smelting furnace for smelting. The smelting temperature is controlled at 740-770℃ and held for 15-25 minutes. After smelting, nitrogen or argon is used to carry the refining agent to refine the melt, remove gas and impurities. The refining time is 10-18 minutes. After standing for 5-12 minutes, the slag is removed to obtain a clean aluminum alloy melt.
4. The method for preparing an aluminum alloy core power cable according to claim 2, characterized in that, In step S2, the continuous casting and rolling temperature is 680–720℃; in step S3, the heat treatment temperature is 500–540℃, and the holding time is 3–8 hours.
5. The method for preparing an aluminum alloy core power cable according to claim 2, characterized in that, In step S4, the total deformation is 85% to 95%, and the cold drawing speed is controlled at 6 to 10 m / min.
6. The method for preparing an aluminum alloy core power cable according to claim 2, characterized in that, In step S7, the finished cable is prepared by stranding the multiple conductor monofilaments obtained in step S6 into an aluminum alloy core wire. The stranding pitch is 12 to 15 times the core wire diameter, and the compression coefficient is not less than 0.
90. A semi-conductive inner shielding layer, a cross-linked polyethylene insulation layer, and a semi-conductive outer shielding layer are simultaneously extruded onto the aluminum alloy core wire using a three-layer co-extrusion process, with the extrusion temperature controlled at 120 to 150°C. Then, the core wire is cross-linked, with the cross-linking temperature controlled at 190 to 320°C and held for 20 to 40 minutes. After cross-linking, the cable is cooled and shaped, and a copper wire shield or copper tape shield is wrapped around the semi-conductive outer shield to form a metal shielding layer with a copper tape thickness of 0.10-0.20 mm. The three wire cores with completed metal shielding are twisted into a cable, and polypropylene filler rope is filled in and wrapped with non-woven fabric for fixation. Then, the isolation layer, steel tape armor layer and outer sheath layer are extruded in sequence. Finally, the conductivity, tensile strength, elongation at break, AC withstand voltage and partial discharge performance of the manufactured cable are tested. After passing the tests, the finished cable is obtained.
7. The method for preparing an aluminum alloy core power cable according to claim 6, characterized in that, The cross-sectional area of the aluminum alloy core wire is as follows: 70-630 mm² for 35kV cable core wire and 70-500 mm² for 10kV cable core wire.
8. The method for preparing an aluminum alloy core power cable according to claim 6, characterized in that, The resistivity of the semiconductive inner shielding layer is ≤800Ω·m, and the resistivity of the semiconductive outer shielding layer is ≤400Ω·m; the thickness of both the semiconductive inner and outer shielding layers of the 10kV cable is 0.7~1.0mm, and the thickness of both the semiconductive inner and outer shielding layers of the 35kV cable is 0.8~1.1mm; the thickness of the cross-linked polyethylene insulation layer of the 10kV cable is 4.2~5.0mm, and the thickness of the cross-linked polyethylene insulation layer of the 35kV cable is 10.0~11.0mm.
9. The method for preparing an aluminum alloy core power cable according to claim 6, characterized in that, The steel strip armor layer adopts a double-layer galvanized steel strip armor structure, wherein the metal strip armor should be spirally wrapped in two layers, and the wrapping should be round and smooth, so that the middle part of the outer metal strip is above the gap of the inner metal strip, and the gap ratio of each metal strip is not greater than 50%.
10. The power cable according to claim 1 or the power cable prepared by the method according to any one of claims 2-9, characterized in that, The cable has a conductor conductivity ≥62.0% IACS, a tensile strength ≥118MPa, and an elongation at break ≥15%.